PENGALAMAN MAHASISWA PUTRI PENGHAFAL AL-QUR’AN DALAM PEMBENTUKAN DISIPLIN SPIRITUAL DI MA’HAD IBNU ZUBAIR - Nanda Febrian; Martin Kustati; Gusmirawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to explore the experiences of female Qur’an memorizers in the process of developing spiritual discipline at Ma’had Ibnu Zubair. The research focuses on how tahfizh activities and the daily structure of ma’had life contribute to shaping students’ patterns of discipline, perseverance, and self-regulation. A qualitative approach with a phenomenological design was employed to uncover the subjective meanings participants attach to tahfizh practices as a form of spiritual training. Data were collected through in-depth interviews, non-participant observations, and documentation of the ma’had’s development programs, involving eight female Qur’an memorizers and one musyrifah. Thematic analysis was used to identify meaningful patterns related to motivation, challenges, habituation strategies, and transformations in spiritual behavior. The findings indicate that tahfizh activities not only enhance memorization quality but also cultivate disciplined living patterns, strengthen spiritual awareness, and improve self-control. The study concludes that the tahfizh-based training at Ma’had Ibnu Zubair significantly contributes to the reinforcement of students’ spiritual discipline and may serve as a model for developing spiritually oriented educational practices in independent tahfizh institutions.